Canine fetus immune system at late development - Roballo, Kelly Cristine Santos (Anim Reprod, 2019)
The immune system is mainly responsible for protecting the organism against agents that may interfere in its homeostasis. Thus, understand how this system develops and operates is very important, for create new therapies to assist this system in its operation, such as its failure. In domestic dogs, few studies show how actually occurs the development, maturation and functioning of the immune system. Therefore, this study demonstrates the development and possible activation of it on dog fetus from late gestational period by in situ and microscopic analyzes.